2020
DOI: 10.3390/biomedicines8100438
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment with Polynucleotides and Hyaluronic Acid Improves Tissue Repair in Experimental Colitis

Abstract: Inflammatory bowel diseases (IBDs) are chronic conditions that can benefit from the combined treatment of adenosine receptor agonists and hyaluronic acid (HA), which, binding the CD44, has pro-survival effects. Therefore, this study investigated the effects of a mixture of polynucleotides and HA in an experimental model of dinitrobenzenesulfonic acid (DNBS)-induced colitis. A group of 40 rats received a single intra-colonic instillation of DNBS, and after 6 h, animals were randomized to receive daily: (i) sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…Primary antibody (caspase-1, 1:250, Cell Signalling, Tucson, AZ, USA) was incubated overnight at 4 °C in a moisturized chamber and the day after the secondary antibody (anti-mouse, Vectastain, Vector, Burlingame, CA, USA) was added and the reaction was visualized with 3,3′-Diaminobenzidine (DAB) (Sigma-Aldrich, Milan, Italy). Counterstaining was performed in Mayer’s haematoxylin [ 67 ]. Appropriate positive and negative controls were used in each test.…”
Section: Methodsmentioning
confidence: 99%
“…Primary antibody (caspase-1, 1:250, Cell Signalling, Tucson, AZ, USA) was incubated overnight at 4 °C in a moisturized chamber and the day after the secondary antibody (anti-mouse, Vectastain, Vector, Burlingame, CA, USA) was added and the reaction was visualized with 3,3′-Diaminobenzidine (DAB) (Sigma-Aldrich, Milan, Italy). Counterstaining was performed in Mayer’s haematoxylin [ 67 ]. Appropriate positive and negative controls were used in each test.…”
Section: Methodsmentioning
confidence: 99%
“…Four studies assessed the potential of Ok- and Om-PDRNs as anti-inflammatory agents to treat inflammatory diseases in several models [ 1 , 2 , 6 , 29 ]. In 2020, one of these studies investigated whether Ok-PDRN exhibited anti-inflammatory activity using Sprague Dawley (SD) rats with ischemic colitis, which was induced via selective devascularization of the descending colon [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ok-PDRN injection enhanced expression of A 2A R, VEGF, and caspase-3, as well as of ERK phosphorylation, but reduced the expression ratio of Bax/Bcl-2 and expression of inflammatory proteins, including COX-2, IL-1β, IL-6, and TNF-α. In 2016, two studies confirmed the anti-inflammatory effect of Om-PDRN in combination with hyaluronic acid (HA) using SD rats with induced colitis (i.e., an inflammatory bowel disease of the gastrointestinal tract) [ 1 , 2 ]. Intra-colonic instillation of dinitrobenzenesulfonic acid (DNBS, 25 mg) and oral administration of dextran sulfate sodium (DSS, 8%) successfully induced experimental colitis in SD rats.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations